Seni Sakral dan Sekuler Suatu Problema Dalam Kehidupan Sosial Religius: Perspektif Yadnya Umat Hindu di Bali - I Putu Gede Parmajaya (Kamaya: Jurnal Ilmu Agama, 2020)
Art in the Hindu perspective in Bali have a very basic position, because it can not be separated from the Hindu community relegius. Ceremony in pretending (holy place) also can not be separated off from the arts such as singing, dancing, musical, painting, art, and literature. Temples, temples and the others are built in such a way as an expression of aesthetics, ethics, and attitudes of the people relegius Hindus in Bali. Pragina or dancers in a spirit of selfless ngayah or work offered various forms of art as a form of devotion presented to Ida Sang Hyang Widhi Wasa (God Almighty). In it there is a sense of devotion and dedication as a form of longing wanted to meet with the source of art itself and the artist wanted to be one with it because the real art of every human being in this world is the spark of art.. The research method used in this research is the Study of Literature. Literature study is research conducted by collecting information from various sources such as books, theses, theses, journals and others to answer and describe the problem formulation in a study. The purpose of this study is to study the Sacred and Secular Arts in Problems in Religious Social Life: The Perspective of Yadnya Hindus in Bali.